2011
DOI: 10.1149/1.3505101
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Conductive Oxide Anode for Solid Oxide Fuel Cells

Abstract: Ceramic anodes comprising infiltrated SrMoO 4 in porous ytttria-stabilized zirconia were investigated. Upon reduction at 1073 K, the electronically insulating SrMoO 4 phase transformed to SrMoO 3 , which has a bulk electronic conductivity of 10 3 S cm −1 under fuel cell conditions. An anode conductivity of 20 S cm −1 was achieved with a low SrMoO 4 loading of 13 vol % of the total anode. The infiltrated composite is dimensionally stable upon redox cycling, and a Pd catalyst was required to achieve good fuel ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 21 publications
2
44
2
Order By: Relevance
“…SrMoO 4 is a stable oxide. It has been reported that reduction of SrMoO 4 in 4 %H 2 /Ar began at 750°C and completed after holding at 800°C for about 3 h [24]. The reducing temperature, 700°C in this study was not enough to convert SrMoO 4 into SrMoO 3 .…”
Section: Conductivity Measurementscontrasting
confidence: 55%
See 1 more Smart Citation
“…SrMoO 4 is a stable oxide. It has been reported that reduction of SrMoO 4 in 4 %H 2 /Ar began at 750°C and completed after holding at 800°C for about 3 h [24]. The reducing temperature, 700°C in this study was not enough to convert SrMoO 4 into SrMoO 3 .…”
Section: Conductivity Measurementscontrasting
confidence: 55%
“…2b, of all samples exhibits an exothermic peak at a temperature around 500°C upon heating is probably due to the reduction of perovskite oxides because endothermic peaks were not observed on cooling therefore it is irreversible indicating not related to phase changes. For samples with second-phase SrMoO 4 , the reduction of SrMoO 4 starts at 750°C in 4 %H 2 /Ar which happens at a much higher temperature [24]. There were some exothermic effects around 700°C on heating which could be related to the phase transformation associated to the reduction of perovskite oxides (Fig.…”
Section: Conductivity Measurementsmentioning
confidence: 97%
“…Our results are consistent with previous infiltrated electrode experimental work, which has reported the conductivity of infiltrated electrodes to be approximately 2% to 5% of the bulk conductivity. 5,6,16,22 …”
Section: Resultsmentioning
confidence: 99%
“…A vast number of published studies can be summarized with a selection of other anode candidates such as: (a) Ru (Sauvet and Fouletier, 2001;Bebelis et al, 2006;Caillot et al, 2007), (b) Cu (Slater and Irvine, 1999;Park et al, 2000), (c) Fluorite (e.g., Cu-CeO 2 -ScSZ; Ye et al, 2007), (d) Tungsten bronze (e.g., (Ba/Sr/Ca/La) 0.6 M x Nb 1−x O 3−δ , where M=Mg, Ni, Mn, Cr, Fe, In, Ti, Sn;Tao and Irvine, 2004), (e) Pyrochlore (e.g., Gd 2 Ti 2 O 7 ) anode materials (Goodenough and Huang, 2007;Sun and Stimming, 2007;Tsipis and Kharton, 2008), (f) LSCM (e.g., La 0.75 Sr 0.25 Cr 0.5 Mn 0.5 O 3−δ ) (Sfeir et al, 2001;Liu et al, 2002;Tao and Irvine, 2004;Ruiz-Morales et al, 2007), SrMoO 4 (Smith and Gross, 2011), and other complex perovskites (Xiao et al, 2010), such as double perovskites (e.g., Sr 2 Mg 1−x Mn x MoO 6−δ; Huang et al, 2006 or Sr 2 CoMoO 6; Zhang et al, 2011), chromites (Vashook et al, 2003), and titanates (Li X. et al, 2009). Although most of the above materials are characterized by high carbon resistance, nevertheless, in most of the cases their practical use is inhibited by the poor electrochemical or catalytic activity, the relatively low electronic conduction, the low thermal and chemical stability, the use of prohibitively expensive materials and/or the high cost of processing for their commercial use (Tsipis and Kharton, 2008;Niakolas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%